Characterization of rare, dormant, and therapy-resistant cells in acute lymphoblastic leukemia - Ebinger, Sarah; Özdemir, Erbey Ziya; Ziegenhain, Christoph; Tiedt, Sebastian; Castro Alves, Catarina; Grunert, Michaela; Dworzak, Michael; Lutz, Christoph; Turati, Virginia A.; Enver, Tariq; Horny, Hans-Peter; Sotlar, Karl; et al. (Cancer cell, 2016)
Tumor relapse is associated with dismal prognosis, but responsible biological principles remain incompletely understood. To isolate and characterize relapse-inducing cells, we used genetic engineering and proliferation-sensitive dyes in patient-derived xenografts of acute lymphoblastic leukemia (ALL). We identified a rare subpopulation that resembled relapse-inducing cells with combined properties of long-term dormancy, treatment resistance, and stemness. Single-cell and bulk expression profiling revealed their similarity to primary ALL cells isolated from pediatric and adult patients at minimal residual disease (MRD). Therapeutically adverse characteristics were reversible, as resistant, dormant cells became sensitive to treatment and started proliferating when dissociated from the in vivo environment. Our data suggest that ALL patients might profit from therapeutic strategies that release MRD cells from the niche.
Gesehen am 30.04.2020